POST POWER SYNDROME PENSIUNAN POLRI - Imelda Antika Restu Mawarti; Gusti Yuli Asih; Retno Ristiasih Utami (MANASA, 2012)
The purpose of this study is to empirically examine the correlation between emotional focused coping and post power syndrome of retired Policemen. The population of this study was 62 retired Policeman at Polda Jateng that retired on January until November 2011. Data was carried out using emotional focused coping scale and post power syndrome scale. The result indicates that there is a negative correlation between emotional focused coping and post power syndrome of retired Policemen.